2011
DOI: 10.1080/01635581.2011.606955
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Combination of Lycopene and Genistein on 7,12- Dimethyl Benz(a)anthracene-Induced Breast Cancer in Rats

Abstract: Breast cancer is one of the most common cancers in women. Carotenoids and soy isoflavones have been postulated to have breast cancer preventive effects. We investigated the potential preventive effects of lycopene and genistein, alone and in combination, on breast cancer development in female Wistar rats treated with 7,12-dimethylbenz[a]anthracene (DMBA), a carcinogen known to induce breast tumors. Mammary carcinogenesis was initiated by a single, oral gavage of DMBA (80 mg/kg body weight) at 55 days of animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…On the other hand, the amount of expressed p53 was potentially decreased in DMBA-administered rats, whereas the amount of expressed bcl-2 was potentially increased as compared to normal control. These findings are supported by the findings of Sahin et al46 who reported that animals administered DMBA had an increased expression of bcl-2 in mammary tissues, and various subtypes of breast cancer have an elevated expression of bcl-2 among them 47. In addition, a recent study48 indicated that the DBMA-induced tumors are apparently the result of p53 inactivation as well as bcl-2 expression activation.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, the amount of expressed p53 was potentially decreased in DMBA-administered rats, whereas the amount of expressed bcl-2 was potentially increased as compared to normal control. These findings are supported by the findings of Sahin et al46 who reported that animals administered DMBA had an increased expression of bcl-2 in mammary tissues, and various subtypes of breast cancer have an elevated expression of bcl-2 among them 47. In addition, a recent study48 indicated that the DBMA-induced tumors are apparently the result of p53 inactivation as well as bcl-2 expression activation.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, honokiol treatment was started 2 weeks prior to the DMBA administration and continued to till the end of the study period. Chemopreventive potential of several natural products were established using similar model and was the basis for present study (Sahin et al, 2011; Bishayee et al, 2013; Mandal and Bishayee, 2015) Among the several animal models of examining promiscuous nature of breast cancer, we chose DMBA model (Barros et al, 2004). The DMBA-induced mammary cancer in rats is one of the standard preclinical animal models for studying chemopreventive drug development against breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…3 Traditional disease treatments which include surgery, chemotherapy, radiotherapy and hormone therapies are not fully effective in treating breast cancer, especially in patients with an advanced stage of the disease. 3,4 Therefore, recent studies have focused on identifying alternative agents that reduce the incidence of the disease and cure it. Synthetic drugs or natural products that are highly selective and less toxic and show anticancer activity can be potential agents in breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%